CHEMampere: Technologies for sustainable chemical production with renewable electricity and CO2, N2, O2, and H2O. (6th May 2022) - Klemm, Elias; Lobo, Carlos M. S.; Löwe, Armin; Schallhart, Verena; Renninger, Stephan; Waltersmann, Lara; Costa, Rémi; Schulz, Andreas; Dietrich, Ralph‐Uwe; Möltner, Lukas; Meynen, Vera; Sauer, Alexander; et al.
Abstract: The chemical industry must become carbon neutral by 2050, meaning that process‐, energy‐, and product‐related CO2 emissions from fossil sources are completely suppressed. This goal can only be reached by using renewable energy, secondary raw materials, or CO2 as a carbon source. The latter can be done indirectly through the bioeconomy or directly by utilizing CO2 from air or biogenic sources (integrated biorefinery). Until 2030, CO2 waste from fossil‐based processes can be utilized to curb fossil CO2 emissions and reach the turning point of global fossil CO2 emissions. A technology mix consisting of recycling technologies, white biotechnology, and carbon capture and utilization (CCU) technologies is needed to achieve the goal of carbon neutrality. In this context, CHEMampere contributes to the goal of carbon neutrality with electricity‐based CCU technologies producing green chemicals from CO2, N2, O2, and H2 O in a decentralized manner. This is an alternative to the e‐Refinery concept, which needs huge capacities of water electrolysis for a centralized CO2 conversion with green hydrogen, whose demand is expected to rise dramatically due to the decarbonization of the energy sector, which would cause a conflict of use between chemistry and energy. Here, CHEMampere's core reactor technologies, that is, electrolyzers, plasma reactors, and ohmic resistance heating of catalysts, are described, and their technical maturity is evaluated for the CHEMampere platform chemicals NH3, NOx, O3, H2 O2, H2, CO, and Cx Hy Oz products such as formic acid or methanol. Downstream processing of these chemicals is also addressed by CHEMampere, but it is not discussed here. Abstract : CHEMampere: achieving carbon neutrality of the chemical industry by using CO2, H2 O, N2, and O2 as raw materials as well as renewable electricity in decentralized factories.